Direct and Indirect Speech Acts of Apologizing in â€œVenom Let There Be Carnageâ€ Movie - Bagus Wahyu Utomo; Zia Hisni Mubarak (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The objective of this research is to identify direct and indirect apologizing speech acts in the utterances of the characters in the movie "Venom let there be carnage". The data source for this study was taken from a movie entitled "Venom let there be carnage" in which many apologizing speech acts are found in it. The method used is a qualitative method. The theory used to identify apologizing speech acts was put forward by Searle & Vanderveken (1985) while to identify the direct and indirect used by the characters in the film using the theory put forward by Yule (1996). The results of this research found 14 types of apologizing speech acts consisting of 12 direct uses and 2 indirect uses.